Antifungal agent tavaborole as a potential broad-spectrum serine and metallo-β-lactamases inhibitorResearch in context - Yan Zhang; Siyuan Yang; Zhaoju Deng; Huangwei Song; Ning Xie; Yunrui Tian; Shangshang Qin; Jifeng Liu; Yong Guo; Dongli Wang; Junfeng Liu; Congming Wu; et al. (EBioMedicine)
Summary: Background: The global emergence and spread of carbapenem-resistant Enterobacteriaceae in clinical settings have driven the search for inhibitors that can counteract carbapenemases. These enzymes include several serine β-lactamases (SBLs, such as KPC) and metallo-β-lactamases (MBLs, such as NDM) that hydrolyse almost all β-lactams including carbapenems. This endeavour has successful developed some SBL inhibitors, including the boron-containing compound vaborbactam. However, the challenge posed by MBLs remains unresolved. Methods: A high-throughput screening was conducted on 1718 FDA-approved drugs as potential adjuvants to meropenem. The synergistic effect was determined by checkerboard assay. The underlying mechanisms were elucidated using enzyme inhibition assays, molecular docking and dynamics simulations. The safety and efficacy were evaluated using a murine model. Findings: We have identified another boron-containing broad-spectrum serine and metallo-β-lactamase inhibitor, the benzoxaborole antifungal agent tavaborole. In vitro, tavaborole enhances the antibacterial activity of multiple β-lactam antibiotics against bacteria producing either SBLs or MBLs. In vivo, injectable administration of tavaborole has demonstrated good safety in mice and has restored the efficacy of meropenem against blaNDM-5 and blaKPC-2-positive bacterial infection in a mouse intraperitoneal model. Tavaborole may effectively inhibit the activity of SBLs and MBLs by covalently bonding with the active serine residue of SBLs and chelating the Zn2+ at the active center of MBLs. Interpretation: Tavaborole shows good potential as an agent for use in combination with β-lactam antibiotics for treating multidrug-resistant Gram-negative bacterial infections. Funding: National Key Research and Development Program of China, National Natural Science Foundation of China, Pinduoduo-China Agricultural University Research Fund.